Pengembangan Sistem Informasi Pembayaran SPP Online Berbasis Web di SMK Negeri 1 Sikur - Hidayat, Khaerul (Lembaga Publikasi Ilmiah Nusantara, 2025)
Payment of Educational Development Contribution (SPP) is one of the routine activities carried out in the school environment, including at SMK Negeri 1 Sikur. The payment process which is still done manually causes various problems, such as late recording, human error, and lack of transparency of information to parents. This study aims to develop a web-based SPP payment information system to simplify the school financial administration process and increase data efficiency and accuracy. The system development method used is the Waterfall model which includes the stages of needs analysis, system design, implementation, testing, and maintenance. This system is built using the PHP programming language with a MySQL database and is accessed via a web browser. The test results using the black-box method show that all system functions run well according to user needs. With this system, the SPP payment process becomes more effective and efficient, and provides more transparent access to information to schools and parents. It is hoped that this system can be a digital solution that supports better school financial governance.